2009
DOI: 10.1016/j.solener.2009.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional finite element model of front surface current flow in cells under non-uniform, concentrated illumination

Abstract: A two-dimensional finite element model of current flow in the front surface of a PV cell is presented. In order to validate this model we perform an experimental test. Later, particular attention is paid to the effects of non-uniform illumination in the finger direction which is typical in a linear concentrator system. Fill factor, open circuit voltage and efficiency are shown to decrease with increasing degree of non-uniform illumination. It is shown that these detrimental effects can be mitigated significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 7 publications
3
39
0
Order By: Relevance
“…Based on above expression, Mellor et al [7], proposed a continuity equation to determine the effective current density distribution of the PV cell surface under non-uniform illumination conditions. This governing equation solved over the solar cell domain is represented by:…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Based on above expression, Mellor et al [7], proposed a continuity equation to determine the effective current density distribution of the PV cell surface under non-uniform illumination conditions. This governing equation solved over the solar cell domain is represented by:…”
Section: Figurementioning
confidence: 99%
“…In most cases, the illumination distribution in a concentrated system is in either a Gaussian or anti-Gaussian distribution. Mellor et al [7] proposed two dimensional finite element modelling (FEM) to simulate the front surface current flow in cells under non-uniform illumination and it explored new ideas for concentrated PV cell modelling. The simulation and experiment work done by Chemisana et al [8] analyzed the electrical performance increase of concentrator solar cells under Gaussian temperature profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The nonuniformly illuminated cell may see irradiance peaks which are several times larger than a uniformly illuminated cell. Nonuniform effects have been studied using experimental [4,5] and modeling approaches [6,7,8]. Among the latter, it has been found that optimizing grid spacing can partially compensate for losses due to nonuniform illumination [8].…”
Section: Introductionmentioning
confidence: 99%
“…C ONCENTRATION photovoltaic (CPV) systems generally exhibit a nonuniform illumination profile along the solar cells they integrate [1]- [4]. The light distribution in such profiles is defined by the design of the concentrator optics and is influenced by structure, optics, and tracking misalignments, which possibly occur during manufacturing/mounting processes or even during its lifetime [2].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the cooling system, the solar cells may present different temperature distributions which also affect the I-V curve differently [6]. The behavior of CPV solar cells operating under both illumination and temperature inhomogeneous profiles are only carelessly reproduced by traditional solar cell models which include an equivalent-lumped series resistance [2]- [4], as shown in Fig. 1(a).…”
Section: Introductionmentioning
confidence: 99%